Influencia de la condición corporal sobre la frecuencia de monta de alpacas machos del CEASA. - Shingón Collahuazo, Gissela Maritza (2021)
This research project aimed to determine the influence of body condition on the frequency of riding in CEASA male alpacas. The study was carried out at the Technical University of Cotopaxi in the Faculty of Agricultural Sciences and Natural Resources 4 male animals and one female were selected for male stimulation, we proceeded to register CC on a scale of 1-5, libido was recorded during the copula of males. The frequency and sampling of semen was performed with the artificial vagina method. The results of CC were on an average scale of 4 (overweight) of 2 and 2.5 (thin), with active sexual behavior in the 3 males recorded through copula, obtaining a sample of ejaculate frequently riding 15-30 minutes and volume of 0.5 semen with a milky white color and spermic concentration of 45-46.5x10/ml in the Neubauer chamber we keep 217.5 million sperm/ml. The frequency of riding, the volume is affected according to body condition, age and size affecting genetic reproduction and improvement in alpacas generating economic and productive losses to producers.